2011
DOI: 10.1162/jocn_a_00077
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interpretations of Intrinsic Connectivity Networks

Abstract: An increasingly large number of neuroimaging studies have investigated functionally connected networks during rest, providing insight into human brain architecture. Assessment of the functional qualities of resting state networks has been limited by the task-independent state, which results in an inability to relate these networks to specific mental functions. However, it was recently demonstrated that similar brain networks can be extracted from resting state data and data extracted from thousands of task-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
1,029
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 951 publications
(1,084 citation statements)
references
References 64 publications
53
1,029
2
Order By: Relevance
“…Several other networks of coherent BOLD activity between remote brain regions have since been identified, including visual, auditory, language and attention networks, and a network called the "default mode network" (DMN) which reduces its activity during attentiondemanding tasks. These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).…”
Section: Introductionsupporting
confidence: 56%
“…Several other networks of coherent BOLD activity between remote brain regions have since been identified, including visual, auditory, language and attention networks, and a network called the "default mode network" (DMN) which reduces its activity during attentiondemanding tasks. These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).…”
Section: Introductionsupporting
confidence: 56%
“…For a detailed description of the anatomical structures in each of the networks, see Beckmann et al 30 To verify that results were not dependent on the choice of network templates, we repeated the analysis using a set of 20 networks from Smith et al 32,34 This analysis yielded similar results to those found for the eightnetwork template (for further details see Supplementary Material M2, Supplementary Figure S2, and Supplementary Figure S3). …”
Section: Eight-network Templatementioning
confidence: 77%
“…Finally, IC8 represented bilateral central sulci, primary somatosensory, and motor regions for the upper body parts (Laird et al. 2011). …”
Section: Resultsmentioning
confidence: 99%